N-valued maximal paraconsistent matrices. Issue 2 (3rd April 2019) - Trybus, Adam
ABSTRACT: The articles Maximality and Refutability Skura [(2004). Maximality and refutability. Notre Dame Journal of Formal Logic, 45, 65–72] and Three-valued Maximal Paraconsistent Logics Skura and Tuziak [(2005). Three-valued maximal paraconsistent logics. In Logika (Vol. 23). Wydawnictwo Uniwersytetu Wrocławskiego] introduced a simple method of proving maximality (in the two distinguished senses) of a given paraconsistent matrix. This method stemmed from the so-called refutation calculus, where the focus in on rejecting rather than accepting formulas. The article A Generalisation of a Refutation-related Method in Paraconsistent Logics Trybus [(2018). A generalisation of a refutation-related method in paraconsistent logics. Logic and Logical Philosophy, 27 (2). doi:10.12775/LLP.2018.002 ] was a first step towards generalising the method. In it, a number of 3-valued paraconsistent matrices were shown maximal. In this article we extend these results to cover a number of n -valued ( n >2) paraconsistent matrices using the same method.